2020
DOI: 10.1093/infdis/jiaa392
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Repeated Infections With Endemic Coronaviruses

Abstract: Abstract Background While the mechanisms of adaptive immunity to pandemic coronavirus SARS-CoV-2 are still unknown, the immune response to the widespread endemic coronaviruses HKU1, 229E, NL63 and OC43 provide a useful reference for understanding repeat infection risk. Methods Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 26 publications
4
142
0
1
Order By: Relevance
“…Deceleration could result from successful control measures or attainment of herd immunity. Should SARS-CoV-2 eventually become endemic (Galanti and Shaman, 2020), it could be critical to have an ongoing community-wide surveillance system to detect newly emerging clusters.…”
Section: Wbe For Mass Surveillance Of Covid-19mentioning
confidence: 99%
“…Deceleration could result from successful control measures or attainment of herd immunity. Should SARS-CoV-2 eventually become endemic (Galanti and Shaman, 2020), it could be critical to have an ongoing community-wide surveillance system to detect newly emerging clusters.…”
Section: Wbe For Mass Surveillance Of Covid-19mentioning
confidence: 99%
“…Seroprevalence studies show that a large percentage of adults have been exposed to these viruses (2). Interestingly, surveillance studies have shown that reinfection with these viruses can occur (3,4), suggesting that immunity is only partially protective. This theory is supported by a challenge study showing that study participants with lower titers of antibodies against HCoV-229E were infected and developed symptoms following experimental inoculation with the virus (5).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent infections were separated by at least eight months, though study participants were tested every four months. In most cases, re-infection occurred, though it could present with mild symptoms and a shortened duration of shedding [12].…”
Section: Discussionmentioning
confidence: 99%